2022
DOI: 10.55003/cast.2022.06.22.008
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fraud Job Recruitment Using Features Reflecting from Real-world Knowledge of Fraud

Abstract: A common method for text-analysis and text-based classification is to process for term-frequency or patterns of terms. However, these features alone may not be able to differentiate fake and authentic job advertisements. Thus, in this work, we proposed a method to detect fake job recruitments using a novel set of features designed to reflect the behavior of fraudsters who present fake information. The features were missing information, exaggeration, and credibility. The features were designed to represent in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…At the same time, values that are too low may result in a model that is too simplistic and unfit. Parameters 'n estimator' with values [50, 100], 'learning rate' with values [0.1, 0.5], and 'max depth' with values [3,5] are also evaluated and compared to find the optimal parameter combination for the Gradient Boosting model's best performance.…”
Section: Parameter Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, values that are too low may result in a model that is too simplistic and unfit. Parameters 'n estimator' with values [50, 100], 'learning rate' with values [0.1, 0.5], and 'max depth' with values [3,5] are also evaluated and compared to find the optimal parameter combination for the Gradient Boosting model's best performance.…”
Section: Parameter Tuningmentioning
confidence: 99%
“…This is because information traffic moves very fast in this digital era. Like online job search, this is one of the most efficient ways that many people worldwide use because of the automatic job recruitment information transfer process [5,6]. Companies do not need to spend too much money to announce job recruitment information, and so do prospective job applicants who do not need to spend more money, time, and effort to obtain this information [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted by Chiraratanasopha and Chayintr [35] focused more on proposing a set of features that relays more information on the behavior of fraudsters who commit ORF. Their research utilised the EMSCAD dataset and demonstrated that information on the exaggeration and credibility can improve the performance measures of ORF detection models.…”
Section: B Related Work In the Orf Domainmentioning
confidence: 99%